Comparison of liver enzymes and sonological grading in nonalcoholic fatty liver - Jwarchan, Bishnu; Lalchan, Subita; Dhakal, Anil; Acharya, Ramesh R (Asian Journal of Medical Sciences, 2020)
Background: Nonalcoholic fatty liver disease (NAFLD) is the leading cause of diffuse liver disease with a global prevalence of 25.24% and progresses to fibrosis and nonalcoholic steatohepatitis (NASH). Diagnosing NAFLD requires demonstration of increased liver fat and ultrasound imaging is widely used for screening. Specific blood tests to diagnose NAFLD and NASH are not yet available and alanine transaminase (ALT) has been used as a marker in population based studies. Aims and Objective: This study was aimed to compare the liver enzymes and sonological grading in NAFLD. Materials and Methods: A prospective hospital based observational study was carried out in 85 patients presenting to medical outpatient department (OPD) with ultrasonogical evidence of nonalcoholic fatty liver (NAFL) from January 2016 to December 2016. The patients were sent for liver enzymes and serum ALT, aspartate aminotransferase (AST) and gamma-glutamyltransferase (GGT) were particularly correlated with the grade of NAFL.Data were collected on a preformed proformaand analyzed using the Statistical Package for the Social Sciences (SPSS)20.0 (SPSS Inc., Chicago, IL, USA). Results: In our study, mean age of the patients was 46.08 years and most of the patients were in age group of 40-60 years. Females (65.88%) were more affected than males (34.12%). There were 71 (83.5%) patients with grade 1 NAFL and 14 (16.5%) patients with grade 2 NAFL. The level of serum ALT increased with higher grades of NAFL. The mean ALT in grade 1 NAFL was 29.14±19.41 and in grade 2 NAFL was 42.19±2157; p= 0.027. Comparison of serum AST and GGT with ultrasonological grading did not show statistical difference. Conclusion: Serum ALT levels correlated with the ultrasonological grades of NAFLD (p = 0.027) whereas AST and ALT did not show statistical correlation with grades of fatty liver. Our study suggests for large sample size study for AST and GGT values relationship with ultrasonological grades.